SAFETY PROBLEMS IN THE CASPIAN REGION IN THE CONTEXT OF CHANGE OF THE GEOPOLITICAL SITUATION - I. I. Abdullayev (Проблемы постсоветского пространства, 2017)
Article is devoted to research of geopolitical processes in Caspian region and to questions of regional security. In article is analyzed the influence on a situation in the region of the western countries. The questions connected with deliveries of hydrocarbonic resources from the countries of the Middle East are considered.